CONTENT ANALYSIS USING USER AND GRATIFICATION THEORY: UNDERSTANDING THE INFLUENCE OF TIKTOK SOCIAL MEDIA PLATFORM ON TRAVEL BEHAVIOUR AMONG GEN Z IN MALAYSIA - Ahmad, Siti Yuliandi; Mohd Rizal, Nur Alfisyah; Abdullah, Nuraini; Zakaria, Nurul Fardini; Hama, Susan (Malaysian Institute of Planners (MIP), 2025)
This study investigates how TikTok influences travel behaviour among Generation Z in Malaysia through the perspective of the Uses and Gratifications Theory. The research addresses the problem of limited scholarly understanding of TikTok’s role in fulfilling multidimensional user needs that shape travel decision-making. The objective is to explore goal-oriented uses of TikTok that influence travel preferences and behaviours in this demographic. A qualitative content analysis was conducted on 30 highly engaged TikTok travel videos, with 300 top comments selected and examined, adhering to ethical standards by utilising only publicly available data. Thematic coding identified cognitive, affective, personal integration, social, and tension release needs. Findings reveal that TikTok operates as more than an entertainment platform, functioning as a dynamic space for information seeking, emotional connection, self-identity validation, peer interaction, and leisure inspiration. These needs influence destination choice, trip planning, and travel experiences by aligning content with personal goals, values, and social aspirations. The platform’s immediacy, visual appeal, and peer-generated recommendations strengthen its role in reducing uncertainty and enhancing travel confidence. The study concludes that TikTok is a critical digital influence channel that shapes both practical and affective dimensions of travel among Generation Z. The implications suggest that tourism marketers, destination managers, and policymakers can optimise TikTok’s potential by designing targeted, identity-relevant content and promoting sustainable tourism narratives that resonate with younger audiences, thereby enhancing destination competitiveness and fostering loyalty.